Cultural Transmission through Dance: Teaching Endeng-Endeng in SMPN 1 Rantau Selatan - Kasmahidayat, Yuliawan; Khanaya, Disty Uni; Suryawan, Ace Iwan (Gondang: Jurnal Seni dan Budaya, 2025)
Endeng-endeng is a traditional Mandailing dance that encapsulates cultural diversity and local wisdom, serving as a medium through which traditional values are sustained amid modern societal shifts. This study investigates the embodiment of local wisdom in the instruction of Endeng-endeng dance among ninth-grade students at SMP Negeri 1 Rantau Selatan. Using a qualitative descriptive method, data were gathered through observation, interviews, and document analysis. Local wisdom in the Mandailing community is reflected in social values, norms, and kinship systems, which are integrated into traditional expressions such as dance. These elements function as intangible cultural assets, reinforcing identity and guiding social behavior. The educational setting is positioned as a critical space for cultural transmission, enabling students to internalize and reproduce these values. Findings indicate that the Endeng-endeng dance is an effective pedagogical tool for instilling moral and social norms, including politeness, communal living, and life guidance. Its integration into formal education supports the preservation of Mandailing cultural heritage and enhances students’ understanding of indigenous knowledge systems. Thus, dance education serves not only as artistic instruction but also as a conduit for intergenerational knowledge transfer and the reinforcement of local identity.